Geopolitics: AI and China; enabling ideology? - Papadopoulou, Dora (Frontiers in Political Science, 2025)
IntroductionThe use of Artificial Intelligence (AI) has changed our understanding of political and social reality. Only recently has AI been brought up in the context of Governance, primarily in relation to the development of National Strategies.MethodsA conceptual and interpretive analysis of China's strategic AI documents (MIC25 and AIDP 2017) is conducted, situating them within the country's political and ideological framework to explore AI's role as an ideological instrument reshaping global power dynamics.ResultsAI has a transformative character, which is a global challenge. While approaching it as performativity or using a human-centric approach has altered the dynamics, China is undoubtedly setting the benchmark for AI. Analysis of China's key strategic documents shows that AI is embedded within a Governance model focused on centralized control, ideological alignment and social stability, using technological innovation to reinforce political legitimacy and contest liberal governance norms.DiscussionThis paper discusses the return of ideology in the context of geopolitics, highlighting China's use of AI as a key example of how it may shift the balance of power. Instead of using AI as an instrument, China mostly applies it as a means of enforcing a power model. China mainly relies on AI as a method to advance a model of power, rather than merely utilizing it as an instrument. As the world moves beyond the US-led liberal international order, the AI battle can be understood fundamentally as a battle of ideologies.